The Limit Of Age Of Marriage Is Related To The Certification Of Marriage (Study Of Early Marriage Reality In Jepara Regency) - Samsul Arifin; Akhmad Khisni; Munsharif Abdul Chalim (Jurnal Daulat Hukum, 2020)
The purpose of this study is to find out the background of the Marriage Worth certificate policy, the reality of early marriage and its impact in Jepara Regency and the Marriage Worth Certificate as an effort to reduce early marriage. The approach in this research is sociology juridical. Data collection methods in this study consisted of primary data obtained directly from the parties concerned. Secondary data consists of Primary legal materials and secondary legal materials namely materials that provide primary legal explanations. As an explanation, tertiary legal materials are given.From this study it can be concluded that the background to the emergence of a Marriage Certificate policy is that divorce rates are increasing, women's reproductive health is problematic, the number of stunting children is caused by teenage mothers and increased domestic violence. Reality the number of early marriages in Jepara Regency increased significantly in 2019 3.16% for men and 3.45% for women. From 9041 marital events dominated by the North Jepara region. The reason is also the local cultural factors that are influenced by the social system and the tradition of young marriage which is inherited in the family. While the impact of making children drop out of school, loss of reproductive rights of children due to having to get pregnant and give birth at a young age, the number of LBW that can lead to the stunting of the Marriage Right Certificate Policy as an effort to prevent early marriage, is very welcomed by various parties and religious leaders as marriage requirements for Catholicism and Hindu. In order to increase family fortune and become a sakinah, mawaddah and rahmah (mercy family).Keywords: Marriage Age Limit; Marriage Certificate; Early Marriage.